Portugal Mineral Resources Cluster Collective Strategy for Sectorial Recognition and Sustainable Development - Lopes, Lopes (2018)
Mineral Resources (MR) as a potential for development of a Country, can only be properly considered if there is an integrated strategy transversal to all activities related to them. Contributions from such different areas, starting with geology, territorial planning, environmental protection, socioeconomic sustainability of populations where MR occurs, associated with market policies, among others, should be analyzed together in an integrated way. The application and subsequent recognition of the Cluster of MR of Portugal constitute therefore a milestone and an important step for its rational management. As an evolution of the Portuguese Stone Cluster where the cluster strategy for the sector proved positive results when related global Portuguese crisis economy occurred, is now the main goal of the “Associação Cluster Portugal Mineral Resources” (ACPMR) to spread the stone sector acquired experience to the Mineral Resources Sector.